THE INFLUENCE OF AUTOMOTIVE INDUSTRIAL WORK PRACTICE COMPETENCIES ON THE READINESS FOR THE AUTOMOTIVE WORLD OF AUTOMOTIVE WORK IN MECHANICAL ENGINEERING STUDENTS, PALANGKA RAYA UNIVERSITY - Sumantri, Febi; Debora; Marko Ayaki Lumbantobing (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
Industrial Work Practice Experience can provide skills and additional knowledge for students to be ready to work. This is because students have seen and are used to the real world of work. When students carry out Industrial Work Practices, students are required to be serious in doing a job so that they have experience that can be useful in the future. If the student is not serious, the student will not be used to the actual world of work environment and the student's skills will be lacking, so there will be no Job Readiness after the student graduates later. This research is a research using quantitative research methods. This research was conducted at the Mechanical Engineering Education Study Program FKIP UPR which was carried out for one Even Semester of the 2021/2022 Academic Year. The population in this study were all students of the Mechanical Engineering Education Study Program, FKIP, University of Palangka Raya who had taken industrial work practices from class 2015 to 2019, totaling 148 people. Then the sample will be taken to be a total of 28 samples of Mechanical Engineering Education students at the University of Palangka Raya.Based on the results of calculating the correlation coefficient as follows: r 0.996 100% based on these results there is a positive correlation of 0.996, so the conclusion is that there is a positive relationship and the value of the correlation coefficient between student automotive practice skills and automotive laboratory management is 0.996. The reliability value of the statement items in the questionnaire for each variable being studied is greater than 0.70. This result indicates that the statement items in the questionnaire are reliable for measuring the variables. Based on the results of the calculation of variable X with a significant level of α 0.05 and dk k-1 21, the value of X²table is 32.671, it turns out that X²count X²table or 3472 32.671 for variable X is normally distributed. And based on the results of the calculation of the Y variable with a significant level of α 0.05 and dk k-1 21, the X²table value is 32.671, it turns out that X²count X²table or 3301 32.671, for the Y variable is normally distributed. The results of the hypothesis test show that variable X (student automotive practice ability) has a significant effect on variable Y (Readiness to Face the World of Automotive Work) and means that H0 is rejected and Ha is accepted.